Translation Problems of English Film Titles into German and their Translation into Indonesian - Dwirika, Leli (Nusantara Science and Technology Proceedings)
This article deals with the translation problems of English film titles into German and their translations into Indonesian. This research aims to address the translation problems of English film titles into German and their translation into Indonesian, in particular the problem of equivalence in the translation from English into German. What are the problems that have arisen and how the titles are translated, whether the transfer of cultural elements also plays an important role? The study uses a descriptive qualitative method with comparative models. The theories used to support this research are the theory of equivalence of Nida and Taber (1974), and the theory of translation methods and procedures of Newmark (1988) and Nord (1993). The data comes from Hollywood films, All Films kino.de, shown in cinemas in Germany in 2020 and 2021 (until September). A total of 159 film titles were translated into German: 111 from 2020, 48 from 2021 (until September), from 12 different film categories. The results of the study showed that there are problems with the translation of film titles that are almost inappropriate for the source language or translated quite differently. In addition, based on the analysis of the data the translation methods were found in the translation of the titles of these films, such as the literal translation, free or descriptive translation, communicative, semantic, idiomatic or faithful methods, as well as various translation methods: additions, transpotition, modulation.This research is intended to provide further insights into the field of translation of different language pairs, in particular into the translation of film titles into Indonesian